ODNOWA CHARYZMATYCZNA I KOŚCIÓŁ WOBEC WYZWAŃ WSPÓŁCZESNOŚCI. TEOLOGICZNA I PASTORALNA AKTUALNOŚĆ WSKAZAŃ JANA PAWŁA II - Sawa, Przemysław (Studia Pastoralne, 2023)
The Second Vatican Council prepared the Church for the requirements of the present and, above all, it began the work of multidimensional renewal (biblical, liturgical, spiritual, structural and pastoral). A particular feature of post-Conciliar Catholicism is also the greater involvement of lay people in the mission of the Church. The new Catholic movements and communities that renew the Church in accordance with their character and vocation are indispensable in this process. An important reality is the Charismatic Renewal (not identified with a single movement), gradually recognized by the Church and appreciated by pastors. An important voice was Saint John Paul II’s teaching who in his speeches and texts showed the directions of the renewal of the Church, also those happening through numerous groups of the Renewal in the Holy Spirit. In this context, John Paul II’s observations expressed during many meetings with Catholic charismatics are extremely valuable. The Pope pointed to the beautiful fruits of the Charismatic Renewal, for example a prayer, biblical, missionary and sacramental revival, and called for active participation in renewing the whole Church and sustaining the ecclesiality of these groups through correct formation and unity with the bishops. Thus, it must be said that the existing and still-emerging communities, bearing charismatic experience, become a powerful stream of grace that renews the Church and enables it to evangelize the contemporary world.